DEVELOPING NEW ICH (nICH) AND ICH-SURGICAL EVACUATION (ICH-SE) SCORE FOR PREDICTING 30-DAY MORTALITY OF SPONTANEOUS INTRACEREBRAL HEMORRHAGE - Tedyanto, Eric Hartono; Pramana, Nyoman Angga Krishna; Widyadharma, I Putu Eka (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Introduction: The Original Intracerebral Hemorrhage (oICH) score has been widely used as a clinical assessment scale that is consistent and reliable for predicting patient mortality. However, the ICH score is sometimes complicated, does not contain an acute complication component of stroke, and is not developed to predict the mortality of patients undergoing surgery. We intended to create a new ICH (nICH) and ICH surgical evacuation (ICH-SE) score to predict 30-day mortality in spontaneous ICH patients. Methods: We conducted a retrospective cohort study involving all spontaneous ICH patients who were hospitalized at Prof. Dr. I.G.N.G. Ngoerah Denpasar between July 2020 and July 2022. To evaluate the relationship between the independent variables and the dependent variable, bivariate analysis will be followed by multivariate logistic regression analysis and the Hosmer and Lemeshow tests. The final model was converted into a scoring system and assessing the final area under the curve (AUC) model to determine predictive mortality value, optimal cut-off point, sensitivity, and specificity value. Results: 265 patients met the requirements, and 83 underwent evacuation surgery. Independent factors associated with ICH patient mortality were high NIHSS on admission, the volume of bleeding (P = 0.016 each), and age >65 years (P = 0.005). Independent factors for good outcomes were pneumonia, sepsis, respiratory failure (p=0.027, p=0.022, p=0.004, respectively), and the absence of mass effect (P<0.001). The nICH score was overall better than the oICH score (AUC 0.864 vs. 0.760). Taking a cut-off value of 2, the nICH score has a sensitivity of 75% and a specificity of 81.4%. Independent factors associated with the mortality of spontaneuous ICH patients who underwent surgery were pneumonia, midline shift >8mm, and intraventricular hemorrhage. By taking a cut-off value of 1, the ICH-SE score has a sensitivity of 71.7% and a specificity of 78.4% with a Youden index (YI) of 0.501. Conclusion: The nICH score proved more effective and reliable than the oICH score in predicting mortality within 30 days of spontaneous ICH patients. This study has also developed an ICH-SE score that can be used to predict 30-day mortality in spontaneous intracerebral hemorrhage patients who are about to undergo an evacuation surgery.